PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR SCOOPY PADA PT MENARA AGUNG KOTA PADANG - Febsri Susanti; Rasyim Jifni Nasri (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
Purchasing decision is a person's attitude to buy or use a product in the form of goods or services that are believed to satisfy him and are willing to bear the risks that may arise. This study aims to determine the relationship between Product Quality and Price with Purchase Decisions. The population in this study are consumers who use Motor Scoopy products at PT. The Great Tower of Padang City as many as 57 people. The sample in this study was 57 people with sampling technique using saturated sampling, where all the population was sampled. Therefore, the data analysis used is statistical analysis in the form of multiple linear regression test. The results of this study indicate that partially, product quality and price variables have a positive influence on purchasing decisions